PENERAPAN MODEL VISUALIZATION AUDITORY KINESTETIC (VAK) DENGAN MULTIMEDIA DALAM PENINGKATAN HASIL BELAJAR IPS TENTANG PERKEMBANGAN TEKNOLOGI PADA SISWA KELAS IV SDN 5 KEBUMEN TAHUN AJARAN 2015/2016 - oftiyani, oki (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Application of Visualization Auditory Kinestetic (VAK) Models with Multimedia in Improving Social Science Learning Outcomes about Development of Technology at The Fourth Grade Students of SDN 5 Kebumen in The Academic Year of 2015/2016. The objectives of this research are: (1) to describe the steps of application VAK models with multimedia, (2) to improve social science learning outcomes about development of technology by using VAK models with multimedia. This research is collaborative Classroom Action Research (CAR) conducted in three cycles, consisting of planning, implementation, observation, and reflection on each cycle. The subject of this research was 30 students. The conclusion of this research is the application of VAK models with multimedia can improve Learning Outcomes of sosial science at the fourth grade students of SDN 5 Kebumen in the academic year of 2015/2016.Keywords: VAK Models, Multimedia, Social ScienceAbstrak: Penerapan Model Visualization Auditory Kinestetic (VAK) dengan Multimedia dalam Peningkatan Hasil Belajar IPS tentang Perkembangan Teknologi pada Siswa Kelas IV Sekolah Dasar. Tujuan penelitian ini adalah: untuk mendeskripsikan penerapan langkah-langkah model VAK dengan multimedia dan meningkatkan hasil belajar IPS tentang perkembangan teknologi melalui model VAK dengan multimedia. Penelitian Tindakan Kelas ini merupakan penelitian kolaboratif yang dilaksanakan dalam tiga siklus. Setiap siklus terdiri dari perencanaan, pelaksanaan, observasi, dan refleksi. Subyek pada penelitian ini berjumlah 30 siswa. Simpulan penelitian ini adalah penerapan model VAK dengan multimedia dapat meningkatkan hasil belajar IPS tentang perkembangan teknologi pada siswa kelas IV SDN 5 Kebumen tahun ajaran 2015/2016. Kata Kunci : Model VAK, Multimedia, IPS